Experimental imaging coding system using three-dimensional subjective speckle structures - Mosso Solano, Edward Fabian (2013)
We propose, and experimentally demonstrate, an optical encoding system employing a three-dimensional subjective speckle distribution as a secure information carrier. An image mask (containing the information to be sent) is illuminated by randomly distributed light. The outgoing wavefront reaches a lens, and thus three-dimensional subjective speckle distributions are generated in the normal direction of the scattering plane. These speckle structures are sampled by registering consecutive planes along the optical axis with a complementary metal-oxide semiconductor camera. Along with the optical parameters (keys), these intensity patterns are sent through independent channels to a receiver. By replicating the original system with the keys and implementing a single-beam multiple-intensity reconstruction, we show that the message recipient needs a minimum set of speckle images to successfully recover the original information. Moreover, intercepting a partial set of speckle images with the keys may not result in a successful interception.